2023
DOI: 10.1038/s41598-023-49603-2
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and atomistic origin of high dielectric permittivity in oxides

Yuho Shimano,
Alex Kutana,
Ryoji Asahi

Abstract: Discovering new stable materials with large dielectric permittivity is important for future energy storage and electronics applications. Theoretical and computational approaches help design new materials by elucidating microscopic mechanisms and establishing structure–property relations. Ab initio methods can be used to reliably predict the dielectric response, but for fast materials screening, machine learning (ML) approaches, which can directly infer properties from the structural information, are needed. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Due to the wide dielectric constant distribution, we adopt the decimal logarithm of the average dielectric constant as the output for our machine learning model. Other research studies showed the same compromise when training dielectric constant predictors . With consistent consideration, the minimum, maximum, and average of some other property values had been calculated as part of the input features, following the logarithmic processing.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Due to the wide dielectric constant distribution, we adopt the decimal logarithm of the average dielectric constant as the output for our machine learning model. Other research studies showed the same compromise when training dielectric constant predictors . With consistent consideration, the minimum, maximum, and average of some other property values had been calculated as part of the input features, following the logarithmic processing.…”
Section: Resultsmentioning
confidence: 90%
“…Other research studies showed the same compromise when training dielectric constant predictors. 42 With consistent consideration, the minimum, maximum, and average of some other property values had been calculated as part of the input features, following the logarithmic processing. The most frequently appearing phase became an input feature and transformed into a one-hot array.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous studies have exclusively concentrated on predicting individual scalar properties, such as the band gap 8−10 and the static dielectric constant, 11,12 without accounting for the frequency dependence of optical properties. While the prediction of spectral properties has only recently emerged in materials science, multiple studies have explored multioutput learning for predicting the electronic and phononic density of states.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, a gap persists in the literature concerning ML surrogate models capable of accurately predicting the frequency-dependent optical properties of solid materials. Previous studies have exclusively concentrated on predicting individual scalar properties, such as the band gap and the static dielectric constant, , without accounting for the frequency dependence of optical properties. While the prediction of spectral properties has only recently emerged in materials science, multiple studies have explored multioutput learning for predicting the electronic and phononic density of states. In the context of optical spectra, a hierarchical-correlation model was utilized to predict the absorption coefficient at different frequencies within the visible range, solely based on the chemical composition within a collection of 69 three-cation metal oxides .…”
Section: Introductionmentioning
confidence: 99%